Factors Affecting Choice Of Health Care Facilities Among The Adults of an Urban Community - Shrestha, Raksha; Adhikari, Sarita (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Health service delivery systems that are safe, accessible, high quality, people-centred, and integrated are critical for moving towards universal health coverage. World Health Organisation is supporting to improve the efficiency and effectiveness of health service delivery systems to all the population not only the patients. This study aims to identify the factors affecting the choice of health care facilities among the adults of an urban community and its association with the selected socio-demographic variables. Methods: A descriptive cross-sectional study was conducted among the community residence with 120 respondents using non-probability purposive sampling technique. Data was collected using semi-structured interview schedule that was analysed by using descriptive statistical methods such as frequency, percentage, mean, standard deviation and inferential statistics such as chi-square test. Result: The findings of the study revealed that majority (60.8%) of the respondents used private health care facilities and there was significant association of the choice of health care facility with the health care services related factors whereas no significant association was found with the selected socio-demographic variables. Conclusions: Based on the study findings, it concluded that various health care services related factors like availability, affordability, acceptability and accessibility factors tends to affect the choice of health care facility